2019
DOI: 10.1590/1678-5150-pvb-5848
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and biometry of the reproductive organs of adult males of Trachemys scripta elegans reared in São Paulo state, Brazil

Abstract: Trachemys scripta elegans is an American underwater chelonian illegally marketed in Brazilian pet shops. When abandoned in nature, it compromises native species, threatening local biodiversity. However, little is known about the body development and structure of its reproductive tract. The objective of the present study was to investigate the morphology and biometry of testis, epididymis and penis, as well as the biometry of the body and secondary sexual characters in this species. Twenty-seven adult males wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In T. s. elegans we observed a unimodal distribution of CL values. This distribution agrees with the results of the studies performed by [ 17 , 18 ]. The mean PL values (19.5±2.3 cm) indicated that all the specimens were sexually mature.…”
Section: Discussionsupporting
confidence: 92%
“…In T. s. elegans we observed a unimodal distribution of CL values. This distribution agrees with the results of the studies performed by [ 17 , 18 ]. The mean PL values (19.5±2.3 cm) indicated that all the specimens were sexually mature.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the testes of Trachemys scripta elegans turtle were oval in shape, bright yellow in color, and were located cranially to the epididymides and caudally to the kidneys (Gradela et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the sixth stage, seminiferous tubules were further expanded, and interstitial connective tissue was only observed in the small spaces among the tubules (Otsuka et al, 2012). The seminiferous of Trachemys scripta elegans turtle comprised of Sertoli and spermatogenic cells, while Leydig cells in the interstitial tissue surrounding the seminiferous tubules (Gradela et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Glans anatomy has been generally described for mammals, where it is typically an inflatable, cap‐shaped expansion of the corpus spongiosum found at the distal end of the penis (Jubilato et al, 2019; Weiss et al, 2012), but it is more poorly understood for other amniote taxa. Studies of the male turtle reproductive anatomy have, until recently, focused on the gross morphologies of noncopulatory glans, not characterizing glans inflation, internal structures, or histological details (Fernandes Araujo Chaves, Viana, Chaves, Miglino, & de Sousa, 2020; Gradela et al, 2019; Larkins & Cohn, 2015; Zug, 1966). Additional comparative studies are required to better define the anatomy and function of glans tissues across amniotes.…”
Section: Introductionmentioning
confidence: 99%